2016
DOI: 10.15740/has/rjahds/7.2/84-90
|View full text |Cite
|
Sign up to set email alerts
|

Aloe vera and its application in dairy and food products

Abstract: Now-a-days peoples are health conscious and are looking forward to have products that carry functional and therapeutic values. Aloe vera (Aloe barbadensis miller) is such a plant that has as many as 200 different types of moleculesof health importance. Due to this, it has been used since ancient time for treating various types of disorders. The Aloe vera contains 1.0-1.5 per cent TS out of which, polysaccharides occupy 55 per cent, sugars 17 per cent, minerals 16 per cent, proteins 7 per cent, lipids 4 per cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, non-significant differences were observed among the treatments in red plum smoothies prepared using Tulsi, Lemongrass and Aloevera. It might be due to variations in moisture contents as reported by Srikanth et al (2016).…”
Section: Shelf Life Assessmentmentioning
confidence: 77%
See 2 more Smart Citations
“…However, non-significant differences were observed among the treatments in red plum smoothies prepared using Tulsi, Lemongrass and Aloevera. It might be due to variations in moisture contents as reported by Srikanth et al (2016).…”
Section: Shelf Life Assessmentmentioning
confidence: 77%
“…It could be attributed to the chemical nature of these natural antioxidants and behavior of milk and fruits components. The bitterness of Aloevera might be another reason of the lower score in sweetness as suggested by Srikanth et al (2016).…”
Section: Shelf Life Assessmentmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, it can be concluded that the product is safe from microbial contamination and can show a Shelf life approx. 10…”
Section: Resultsmentioning
confidence: 99%
“…Aloe vera gel or juice are used to incorporate in different dairy products like flavoured milk, ice cream, Dahi, yoghurt, Lassi and also food products like RTS and edible coatings etc. (Srikanth, Keerthi, Kartikeyan, S., Adarsh, Kalla, Punitha, K. and Sharanabasava (2016) [10] .…”
Section: Introductionmentioning
confidence: 99%